GAMBARAN PARENTAL INVOLVEMENT PADA ORANG TUA DENGAN ANAK AUTISM SPECTRUM DISORDER (ASD) - Nisa, Wardatun; Fikrie, Fikrie; Amalia Aprianty, Rizqi (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
The increasing number of children with Autism Spectrum Disorder (ASD) poses significant challenges for parents, particularly regarding their caregiving involvement. This study explores the parental involvement of those who do not implement a Home Program, using a phenomenological approach and Epstein’s six-dimensional framework. Data were collected through semi-structured interviews and observations with two mothers whose children had undergone therapy for at least six months. Findings reveal that only the parenting and communicating dimensions were adequately fulfilled, while volunteering, learning at home, decision-making, and collaborating with the community remained low. The study highlights the urgent need for community-based interventions, practical Home Program training, and emotional capacity-building for parents. By focusing specifically on parents who do not implement Home Programs and applying Epstein’s full framework, this study offers a new perspective on understanding caregiving involvement among families of children with special needs. ABSTRAK Jumlah anak dengan Autism Spectrum Disorder (ASD) terus meningkat, menimbulkan tantangan signifikan bagi orang tua, khususnya dalam keterlibatan pengasuhan. Studi ini mengeksplorasi keterlibatan orang tua anak ASD yang tidak menjalankan Home Program, menggunakan pendekatan fenomenologis dan enam dimensi Epstein sebagai kerangka analisis. Data diperoleh melalui wawancara semi-terstruktur dan observasi terhadap dua ibu dengan anak ASD yang telah menjalani terapi minimal enam bulan. Temuan menunjukkan bahwa hanya dimensi parenting dan Communicating yang tergolong baik, sedangkan volunteering, Learning At Home, Decision-Making, dan collaborating with the community masih rendah. Studi ini menyoroti kebutuhan intervensi berbasis komunitas, pelatihan Home Program, dan penguatan kapasitas emosional orang tua. Fokus khusus pada orang tua yang tidak menjalankan Home Program serta penggunaan menyeluruh kerangka Epstein memberikan sudut pandang baru dalam memahami dinamika keterlibatan pengasuhan pada keluarga dengan anak berkebutuhan khusus.